Physical activity, mental health and well-being of adults during initial COVID-19 containment strategies: A multi-country cross-sectional analysis. Issue 4 (April 2021) - Faulkner, James; O'Brien, Wendy J.; McGrane, Bronagh; Wadsworth, Daniel; Batten, John; Askew, Christopher D.; Badenhorst, Claire; Byrd, Erin; Coulter, Maura; Draper, Nick; Elliot, Catherine; Fryer, Simon; et al.
Abstract: Objectives: To assess physical activity (PA), mental health and well-being of adults in the United Kingdom (UK), Ireland, New Zealand and Australia during the initial stages of National governments' Coronavirus disease (COVID-19) containment responses. Design: Observational, cross-sectional. Methods: An online survey was disseminated to adults (n = 8, 425; 44.5 ± 14.8y) residing in the UK, Ireland, New Zealand and Australia within the first 2-6 weeks of government-mandated COVID-19 restrictions. Main outcome measures included: Stages of Change scale for exercise behaviour change; International Physical Activity Questionnaire (short-form); World Health Organisation-5 Well-being Index; and the Depression Anxiety and Stress Scale-9. Results: Participants who reported a negative change in exercise behaviour from before initial COVID-19 restrictions to during the initial COVID-19 restrictions demonstrated poorer mental health and well-being compared to those demonstrating either a positive-or no change in their exercise behaviour ( p  < 0.001). Whilst women reported more positive changes in exercise behaviour, young people (18-29y) reported more negative changes (both p  < 0.001). Individuals who had more positive exercise behaviours reported better mental health and well-being ( p  < 0.001). Although there were no differences in PA between countries, individuals in New Zealand reported better mental health and well-being ( p  < 0.001). Conclusion: The initial COVID-19 restrictions have differentially impacted upon PA habits of individuals based upon their age and sex, and therefore have important implications for international policy and guideline recommendations. Public health interventions that encourage PA should target specific groups (e.g., men, young adults) who are most vulnerable to the negative effects of physical distancing and/or self-isolation.